2014
DOI: 10.1002/humu.22729
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inSNRPB, Encoding Components of the Core Splicing Machinery, Cause Cerebro-Costo-Mandibular Syndrome

Abstract: Cerebro-costo-mandibular syndrome (CCMS) is a developmental disorder characterized by the association of Pierre Robin sequence and posterior rib defects. Exome sequencing and Sanger sequencing in five unrelated CCMS patients revealed five heterozygous variants in the small nuclear ribonucleoprotein polypeptides B and B1 (SNRPB) gene. This gene includes three transcripts, namely transcripts 1 and 2, encoding components of the core spliceosomal machinery (SmB' and SmB) and transcript 3 undergoing nonsense-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 21 publications
1
47
0
1
Order By: Relevance
“…In 2014, Lynch et al employed exome sequencing to identify dominant, heterozygous mutations in SNRPB, encoding small nuclear ribonucleoprotein polypeptides B and B1, as a cause of CCMS (9). In an independent exome sequencing study, Bacrot et al recently identified de novo mutations in the same alternative exon of SNRPB as Lynch et al, in five CCMS patients (10). Each snRNP contains specific protein and RNA components plus a core of seven proteins, known as the Sm proteins, common to all snRNPs.…”
Section: Cerebrocostomandibular Syndromementioning
confidence: 94%
See 2 more Smart Citations
“…In 2014, Lynch et al employed exome sequencing to identify dominant, heterozygous mutations in SNRPB, encoding small nuclear ribonucleoprotein polypeptides B and B1, as a cause of CCMS (9). In an independent exome sequencing study, Bacrot et al recently identified de novo mutations in the same alternative exon of SNRPB as Lynch et al, in five CCMS patients (10). Each snRNP contains specific protein and RNA components plus a core of seven proteins, known as the Sm proteins, common to all snRNPs.…”
Section: Cerebrocostomandibular Syndromementioning
confidence: 94%
“…Besides the classic features of CCMS, scoliosis, decreased height, conductive hearing loss and down-slanting palpebral fissures were occasionally present in the SNRPB mutation-positive patients (9,10), and neurological and cognitive defects were reported in a small proportion of the cohort reported by Lynch et al Although it had previously been suggested that psychomotor retardation in CCMS may be a secondary effect linked to hypoxia due to respiratory distress at birth, it is also plausible that when present, this phenotype is due to a primary defect in splicing of neurodevelopmental genes.…”
Section: Cerebrocostomandibular Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mutations in SmB were linked to cerebro-costo-mandibular syndrome (Bacrot et al, 2015). The multi-domain protein RBM5 promotes FAS exon 6 skipping and it has been proposed that for this activity the protein modulates splice site pairing after the competing 5’ and 3’ splice sites have been recognized by U1 and U2 snRNPs, respectively (Bonnal et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of CDG type II with a mutation in COG1 (component of oligomeric golgi complex 1, involved in glycosylation) in patients with RS and features resembling CCMS revealed that a metabolic disorder might also be the underlying cause of RS (Zeevaert et al, ). Curiously, CCMS is also caused by mutation in SNRPB , encoding the small nuclear ribonucleoprotein polypeptides B and B1 and a core component of the spliceosome required for processing of pre‐mRNA into the mature mRNA form in all cells (Bacrot et al, ).…”
Section: Genetic Perspectivementioning
confidence: 99%